Feto acardio en embarazo gemelar de 24.1 semanas de gestación. - Osorio Ronquillo, Andrea Lilibeth (2020)
Twin pregnancies can trigger a series of complications among them are fetal malformations and one of the most serious is the fetus Arcadio, Acéfalo that occurs in monocorial twin gestations. It is believed that the origin of this malformation is due to the abnormal vascular anastomosis of the placenta that causes the main cephalic involution of one of the fetuses which is always unfeasible. This defect can be originated in early stages of embryonic development due to vascular anastomosis that condition the inverted arterial flow to the acardio twin, in which the healthy twin will suffer multiple consequences by having to fulfill his cardiac function and of his brother, the fetus is a very rare malformation but since ancient times it has evolved with respect to the way of being called from naming him headless monster to a malformed fetus not compatible with life.